Segregation of yeast nuclear pores - Khmelinskii, Anton; Keller, Philipp J.; Lorenz, Holger; Schiebel, Elmar; Knop, Michael (Nature, 2010)
Arising from: Z. Shcheprova, S. Baldi, S. B. Frei, G. Gonnet & Y. Barral Nature 454, 728-734 (2008). During mitosis in Saccharomyces cerevisiae, senescence factors such as extrachromosomal ribosomal DNA circles (ERCs) are retained in the mother cell and excluded from the bud/daughter cell. Shcheprova et al. proposed a model suggesting segregation of ERCs through their association with nuclear pore complexes (NPCs) and retention of pre-existing NPCs in the mother cell during mitosis. However, this model is inconsistent with previous data and we demonstrate here that NPCs do efficiently migrate from the mother into the bud. Therefore, binding to NPCs does not seem to explain the retention of ERCs in the mother cell.
Gesehen am 11.08.2017